The browning kinetics of the non-enzymatic browning reaction in L-ascorbic acid/basic amino acid systems - YU,Ai-Nong (2018)
Abstract Under the conditions of weak basis and the reaction temperature range of 110-150 °C, lysine, arginine and histidine were reacted with L-ascorbic acid at equal amount for 30-150 min, respectively and the formation of browning products was monitored with UV–vis spectrometry. The kinetic characteristics of their non-enzymatic browning reaction were investigated. The study results indicated that the non-enzymatic browning reaction of these three amino acids with L-ascorbic acid to form browning products was zero-order reaction. The apparent activation energies for the formation of browning products from L-ascorbic acid/lysine, L-ascorbic acid/arginine and L-ascorbic acid/histidine systems were 54.94, 50.08 and 35.31kJ/mol. The activation energy data indicated the degree of effects of reaction temperature on non-enzymatic browning reaction. Within the temperature range of 110-150 °C, the reaction rate of L-ascorbic acid/lysine system was the fastest one, followed by that of the L-ascorbic acid/arginine system. The reaction rate of L-ascorbic acid/histidine system was the slowest one. Based on the observed kinetic data, the formation mechanisms of browning products were proposed.